Gender Differences in Household Coping Strategies for COVID-19 in Kenya - Xu, Yuanwei (Washington, DC: World Bank, 2022)
Understanding how different households cope with COVID-19 among a vulnerable population is important for the policy design aiming at relieving hunger and poverty in a low income setting. This paper uses original household data from five waves of a phone survey conducted between May 2020 and June 2021 in Kenya (sample size 31,715) and investigates the gender differences in household coping strategies during the COVID-19 shock. It finds that female-headed households are less likely to cope by selling assets or taking loans, compared with male-headed households. Instead, femaleheaded households rely more on social networks to cope. No difference in coping by reducing meals is observed across these two types of households. This paper documents that the reasons behind the gender difference include that female-headed households are poorer, and they are more likely to rely on friends and family to cope with shocks even prior to the COVID-19 shock. The findings suggest that widowed and divorced women are in high need of relief programs, and governments should provide easily accessible loans to avoid negative impacts in the long term from households selling assets.